2013
DOI: 10.1080/10503307.2013.807377
|View full text |Cite
|
Sign up to set email alerts
|

Predicting outcome of Internet-based treatment for depressive symptoms

Abstract: In this study we explored predictors and moderators of response to Internet-based cognitive behavioral therapy (CBT) and Internet-based problem-solving therapy (PST) for depressive symptoms. The sample consisted of 263 participants with moderate to severe depressive symptoms. Of those, 88 were randomized to CBT, 88 to PST and 87 to a waiting list control condition. Outcomes were improvement and clinically significant change in depressive symptoms after 8 weeks. Higher baseline depression and higher education p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 32 publications
8
39
0
Order By: Relevance
“…The finding that higher pre-treatment depression was associated with a higher likelihood of improvement across both groups seems plausible and is consistent with other research (Ruwaard et al, 2009;Spek et al, 2008;Warmerdam et al, 2013). Greater severity leaves more room for improvement and thus significant change in reduction of depressive symptoms.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The finding that higher pre-treatment depression was associated with a higher likelihood of improvement across both groups seems plausible and is consistent with other research (Ruwaard et al, 2009;Spek et al, 2008;Warmerdam et al, 2013). Greater severity leaves more room for improvement and thus significant change in reduction of depressive symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, these ranges are based on the mean scores of the current study and may not generalize to other studies. Lastly, definitely not all possible predicting/moderating variables were captured in the current study; for example, number of previous episodes, education level, and dysfunctional attitudes, or other work-related factors, such as low-effort reward imbalance and lack of control over decision at work, could have also predicted outcome or moderated the effects of IPST (Bockting et al, 2006;Donker et al, 2013;Spek et al, 2008;Warmerdam et al, 2013). Future studies should aim to consider these variables as well as long-term effects with respect to depression onset (van Zoonen et al, 2014).…”
Section: Limitations and Future Researchmentioning
confidence: 97%
See 2 more Smart Citations
“…This might have affected the results since CBT has been found to be more effective for university students (Cuijpers, Ebert, Acarturk, Andersson, & Cristea, 2016b) and specific studies on internet-based treatment have shown that individuals with a university degree receive better outcomes (Warmerdam, van Straten, Twisk, & Cuijpers, 2013). It could be a problem for dissemination into regular health care, since ICBT might only fit a small well-educated group of patients.…”
Section: Limitationsmentioning
confidence: 99%